What will you be? [book with audioplayer] - Méndez, Yamile Saied ([Library Ideas, LLC], 2021)
From Yamile Saied Méndez, acclaimed author of Where Are You From?, comes a stunning lyrical picture book that tells the story of one girl who is always asked a simple question: What will you be when you grow up? "Méndez and Alizadeh create a balance between the abstract and concrete by letting the child imagine the future but with Abuela's guidance and support. A sweet read to share with loved ones." -Kirkus (starred review) "Turning a common question of childhood into a substantive quest, this imaginative set of plans will have other children charting their own course through the stars." -School Library Journal What will you be when you grow up? A young girl dreams about all the endless possibilities, sparking a sense of wonder, curiosity, and growth. With her abuela's loving guidance, she learns her potential is limitless. Yamile Saied Méndez's powerful, lyrical text and Kate Alizadeh's colorful, stunning art are a radiant celebration of family, love, and community.